On the Numerical Determination of the Density and Energy Spatial Distributions relevant for in-Plasma β-Decay Emission Estimation - Galatà, A.; Mascali, D.; Mishra, B.; Naselli, E.; Pidatella, A.; Torrisi, G. (Frontiers in Physics, 2022)
Aim of the PANDORA (Plasmas for Astrophysics, Nuclear Decays Observation and Radiation for Archeometry) project is the in-plasma measurements of decay rates of beta radionuclides as a function of the ionization stage. In this view, a precise calculation of plasma electrons density and energy is mandatory, being responsible for ions’ creations and their spatial distribution following plasma neutrality. This paper describes the results of the INFN simulation tools applied for the first time to the PANDORA plasma, including electromagnetic calculations and electrons’ dynamics within the so-called self-consistent loop. The distribution of the various electrons’ population will be shown, with special attention to the warm component on which depends the obtained ions’ charge state distribution. The strict relation of the results with the evaluation of the in-plasma nuclear decays will be also explained.